Prioritising the sustainable development goals using a network approach - Kunčič, Aljaž (Teorija in praksa, 2019)
The Sustainable Development Goals (SDGs) are central to the operationalization of the 2030 Agenda for Sustainable Development. Both represent an ambitious developmental framework whose potential to focus on smart policies and prioritise measures that bring the maximum impact on the highest number of SDGs is crucial for achieving progress. We propose this can be accomplished using the criteria of efficiency in policy targeting of SDGs. In particular, by examining the links among SDGs, identifying positive and negative connections, and the core goals and tightly knit communities in the developmental networks of today and tomorrow. Utilising the SDGs' interconnected nature for developmental planning and comparing the characteristics of developmental networks may be the missing component in accelerating sustainable development.
Keywords: Agenda 2030; Analiza omrežij; Cilji trajnostnega razvoja; Človekov razvoj; Human development; Network analysis; Organizacija združenih narodov; Sustainable development; Trajnostni razvoj